The impact of dentists' availability in delivering dental care in Florida Elementary Schools. (11th October 2022) - Ma, Simin; Serban, Nicoleta; Dehghanian, Amin; Tomar, Scott L.
Abstract: Objective: This study evaluates the dentists' availability to deliver preventive dental care to children in schools and the impact of school‐based programs on access. Methods: The study population included Florida elementary‐school children, differentiated by dental insurance (Medicaid, CHIP, private, or none). We considered the implementation of school‐based programs using optimization modeling to (re)allocate the dentists' caseload to schools to meet demand for preventive care under resource constraints. We considered multiple settings for school‐based program implementation: (i) school prioritization; and (ii) dentists' participation in public insurance. Statistical inference was used to identify communities to improve access and reduce disparities. Results: School‐based programs reduced unmet demand (3%–12%), being more efficient if prioritizing schools in communities targeted to improve access. The access improvement varied by insurance status and geography. Uninsured urban children benefited most from school‐based programs, with 15%–75% unmet need reduction. The percentage of urban communities targeted to improve access decreased by 12% against no‐school program. Such percentage remained large for suburban (15%–100%) and rural (50%–100%) communities. Disparity in access for public‐insured vs. private‐insured children persisted under school‐based programs (32%–84% identified communities). Conclusion: School‐based programs improve dental care access; the improvement was however different by insurance status, with uninsured children benefiting the most. Accounting to the dentists' availability in prioritizing schools resulted in effective resource allocation to school‐based programs. Access disparities between public and private‐insured children did not improve; school‐based programs shifted resources from public‐insured to uninsured. School‐based programs are effective in addressing access barriers to those children experiencing them most.